Association of Healthy Diet and Physical Activity With Breast Cancer: Lifestyle Interventions and Oncology Education - Jia, Tiantian; Liu, Yufeng; Fan, Yuanyuan; Wang, Lintao; Jiang, Enshe (Frontiers in Public Health, 2022)
Global cancer statistics suggest that breast cancer is the most diagnosed cancer in females, with an estimated 2.3 million new cases reported in 2020. Observational evidence shows a clear link between prevention and development of invasive breast cancer and lifestyle-based interventions such as a healthy diet and physical activity. Recent findings reveal that even minimal amounts of daily exercise and a healthy diet reduced the risk of breast cancer, mitigated the side effects of cancer treatment, and stopped the recurrence of cancer in the survivors. Despite the myriad benefits, implementation of these lifestyle interventions in at-risk and survivor populations has been limited to date. Given the need to disseminate information about the role of physical activity and nutrition in breast cancer reduction, the review aimed to presents the recent scientific outreach and update on associations between the lifestyle interventions and breast cancer outcomes to narrow the gap and strengthen the understanding more clearly. This review covers more direct, detailed, and updated scientific literature to respond to frequently asked questions related to the daily lifestyle based interventions and their impact on breast cancer risk and survivors. This review also highlights the importance of the oncology provider’s job and how oncology education can reduce the breast cancer burden.